(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This paper examines how digitization has affected education and the job market, concentrating on the economy of Uzbekistan. The analysis highlights the significance of competency-based human resource management in finding and developing competent persons while taking into account the growth of technology and its implications on employment structures. The study uses a mixed-method approach to investigate the relationship between labor productivity and digitalization. It combines empirical analysis using structural equation modeling (SEM) with a review of the literature and the development of a theoretical framework. The results emphasize the value of investing in the development of digital skills and point to a considerable beneficial influence of variables like years of education, internet usage, e-government development index (EGDI), and mobile cellular subscriptions on labor productivity. However, there is no discernible relationship between worker productivity and variables like graduation rates and enrollment in schools. In order to prepare the labor force for the digital revolution and promote economic growth in Uzbekistan and other comparable contexts, the study emphasizes the necessity of strategic measures.